Better recognition, diagnosis and management of non‐IgE‐mediated cow's milk allergy in infancy: iMAP—an international interpretation of the MAP (Milk Allergy in Primary Care) guideline. Issue 1 (23rd August 2017) - Venter, Carina; Brown, Trevor; Meyer, Rosan; Walsh, Joanne; Shah, Neil; Nowak‐Węgrzyn, Anna; Chen, Tong‐Xin; Fleischer, David M.; Heine, Ralf G.; Levin, Michael; Vieira, Mario C.; Fox, Adam T.
Abstract: Cow's milk allergy (CMA) is one of the most common presentations of food allergy seen in early childhood. It is also one of the most complex food allergies, being implicated in IgE‐mediated food allergy as well as diverse manifestations of non‐IgE‐mediated food allergy. For example, gastrointestinal CMA may present as food protein induced enteropathy, enterocolitis or proctocolitis. Concerns regarding the early and timely diagnosis of CMA have been highlighted over the years. In response to these, guideline papers from the United Kingdom (UK), Australia, Europe, the Americas and the World Allergy Organisation have been published. The UK guideline, 'Diagnosis and management of non‐IgE‐mediated cow's milk allergy in infancy—a UK primary care practical guide' was published in this journal in 2013. This Milk Allergy in Primary Care (MAP) guideline outlines in simple algorithmic form, both the varying presentations of cow's milk allergy and also focuses on the practical management of the most common presentation, namely mild‐to‐moderate non‐IgE‐mediated allergy. Based on the international uptake of the MAP guideline, it became clear that there was a need for practical guidance beyond the UK. Consequently, this paper presents an international interpretation of the MAP guideline to help practitioners in primary care settings around the world. It incorporates further published UK guidance, feedback from UK healthcare professionals and affected families and, importantly, also international guidance and expertise.